EVALUATION OF TABLETED MICROSPHERES OF DIPYRIDAMOLE - (:unkn) unknown (MARCEL DEKKER INC, 1995)
Microspheres of dipyridamole were prepared by solvent evaporation methods. The effect of additives Avicel PH 101, and beta cyclodextrin on the release rate of tableted microspheres were studied. Incorporating Avicel or beta cyclodextrin increased the dipyridamole release rates in tableted microspheres. Beta cyclodextrin was found to be a good additive for microsphere tablets to increase the drug release rates without causing disintegration.
Keywords: DISSOLUTION